Pengaruh Gaya Kepemimpinan, Pelatihan Kerja, dan Kompensasi terhadap Kinerja Karyawan di PO Gunung Harta Ponorogo - Ferawidianti Widianti; Kenlies Era Rosalina Marsudi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Employee performance is the final result achieved by individuals in the form of goods or services, which must be by the agreed quality or standards in terms of cost, time, quality, and quantity. At the Gunung Harta Ponorogo Branch Office, various performance problems have emerged, such as bus delays, decreased ticket sales, customer complaints regarding unsatisfactory service, unfriendly attitudes, delays in departure, lack of coordination between teams, and lack of responsiveness. This study aims to analyze the effect of leadership style, job training, and compensation on employee performance partially and simultaneously. The method used is quantitative, with data collection through questionnaires to 50 Gunung Harta Ponorogo Branch Office employees using saturated samples. Instrument testing includes validity and reliability tests, while data analysis is carried out by descriptive analysis, classical assumption test, and multiple regression analysis. The findings show that leadership style positively and significantly influences employee performance. Then job training has a positive and significant influence on employee performance. And finally compensation also has a positive and significant influence on employee performance.